Selenium dynamics in cereal biofortification: optimising fertiliser strategies and assessing residual fate - Ramkissoon, Chandnee (2020)
Selenium (Se) is an essential micronutrient for humans and animals and hence, a low intake of Se in the diet can lead to health problems. The application of Se fertilisers to staple crops, a process called agronomic biofortification, can effectively improve humans’ Se intake levels. The overarching aim of this study was to develop improved strategies for Se biofortification through an enhanced understanding of Se dynamics in arable systems.